Respuesta :

Answer:

(44, - 27 )

Step-by-step explanation:

Given the 2 equations

5x + 8y = 4 → (1)

2x + 3y = 7 → (2)

Multiplying (1) by 2 and (2) by - 5 , then adding the result will eliminate x

10x + 16y = 8 → (3)

- 10x - 15y = - 35 → (4)

Add (3) and (4) term by term to eliminate x

y = - 27

Substitute y = - 27 into either of the 2 equations and solve for x

Substituting into (2)

2x + 3(- 27) = 7

2x - 81 = 7 ( add 81 to both sides )

2x = 88 ( divide both sides by 2 )

x = 44

solution is (44, - 27 )

ACCESS MORE